Appearance of a Proper Name and its Various Neological Forms in Hungarian Political and Media Discourse - Kovács, Máté (Populismo y propaganda: entre el presente y el pasado, 2020)
The proper name Soros appeared frequently in Hungarian political and media discourse during the last couple of years. This name served as a basis for the composition and derivation of a large number of neological expressions used in contemporary Hungarian. The main purpose of this article is to analyse how various forms composed and derived on the basis of the proper name Soros are used in discourse and to show how these forms contribute to convey a populist ideology.